Association between personality traits and job performance among secondary school teachers - Mahmud, Norashikin (2015)
This paper examines the association between personality traits and job performance among Malaysian public secondary school teachers. It focuses on Big Five personality dimensions: Openness to Experience, Conscientiousness, Extraversion, Agreeableness and Neurot icism. A total of 954 questionnaires were distributed to teachers in eight public secondary schools, however only 489 usable responses were used. Descriptive, correlation and multiple regression statistics are used to analyse the data. The findings reveale d that there is a positive association between Openness to Experience and Agreeableness and job performance. On the contrary, there is a negative association between Neuroticism and job performance. The most predictive trait that influences job performance is Neuroticism and followed by Openness to Experience. The implications of this study suggests that understanding the influence of personality traits on job performance is essential and its justify the use of personality test by the Ministry of Education Malaysia for recruiting and selecting suitable candidates to become an educator. The Ministry of Education Malaysia is aiming to implement a world - class teacher education to ensure that the teachers are competent to meet the national inspiration